2011
DOI: 10.1186/1471-2334-11-129
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage revision surgery with preformed spacers and cementless implants for septic hip arthritis: a prospective, non-randomized cohort study

Abstract: BackgroundOutcome data on two-stage revision surgery for deep infection after septic hip arthritis are limited and inconsistent. This study presents the medium-term results of a new, standardized two-stage arthroplasty with preformed hip spacers and cementless implants in a consecutive series of adult patients with septic arthritis of the hip treated according to a same protocol.MethodsNineteen patients (20 hips) were enrolled in this prospective, non-randomized cohort study between 2000 and 2008. The first st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 28 publications
3
97
0
1
Order By: Relevance
“…Since then, several authors reported on the outcomes using those preformed hip spacers (Spacer-G and InterSpace ® Hip) in the interim period of two-stage revision arthroplasty [3][4][5][6][7][8][9][10][11][12]. Most of the studies are limited due to a small number of included cases or due to a relatively short follow-up time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since then, several authors reported on the outcomes using those preformed hip spacers (Spacer-G and InterSpace ® Hip) in the interim period of two-stage revision arthroplasty [3][4][5][6][7][8][9][10][11][12]. Most of the studies are limited due to a small number of included cases or due to a relatively short follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…The inner part of the spacer usually contains a stainless steel rod, which is covered by antibiotic loaded cement. The cement is preloaded by the manufacturer most often with 1.9 g gentamicin sulfate [3][4][5][6][7][8][9][10][11][12]. Surgeon-made spacers are intraoperatively preformed spacers ranging from hand-made techniques using a bulb syringe to fashion a femoral head, to molded systems with or wihtout a metal endo-skeleton, while in the majority of cases, metal endoskeleton was not used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent decades, the risk decreased by the use of laminar airflow, antibiotic prophylaxis, antibiotic loaded bone cement (PMMA), rigorous hygiene standards, and standardized surgical procedures [3,[5][6][7]. Despite these efforts, infection after implantation of total hip arthroplasty (THA) is still a serious problem for patients, physicians and the general public [2].…”
Section: Introductionmentioning
confidence: 99%